Pengaruh Motivasi Kerja dan Efikasi Diri Terhadap Kepuasan Kerja yang dimediasi Kualitas Kerja Pegawai Dinas Pendidikan Kota Makassar - Anjelina Afdar; Romansyah Sahabuddin; Muhammad Ichwan Musa; Rezky Amalia Hamka; Widhi Nugraha S.D. (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of work motivation and self-efficacy on job satisfaction, with work quality serving as a mediating variable, among employees of the Makassar City Education Office. Employing a quantitative approach, data were collected from 63 respondents selected using the Slovin formula from a total population of 168 employees. Data analysis was conducted using multiple linear regression via SmartPLS software. The results indicate that work motivation and work quality have a positive and significant effect on job satisfaction. However, self-efficacy does not have a significant direct effect on job satisfaction in this context. Work quality was found to act as a significant mediator linking work motivation and self-efficacy to employee job satisfaction. These findings underscore the importance of the agency focusing on strengthening motivation and work quality standards to create a satisfying work environment for employees.